2019
DOI: 10.3390/ijms20143598
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death in the Kidney

Abstract: Apoptotic cell death is usually a response to the cell’s microenvironment. In the kidney, apoptosis contributes to parenchymal cell loss in the course of acute and chronic renal injury, but does not trigger an inflammatory response. What distinguishes necrosis from apoptosis is the rupture of the plasma membrane, so necrotic cell death is accompanied by the release of unprocessed intracellular content, including cellular organelles, which are highly immunogenic proteins. The relative contribution of apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 182 publications
(213 reference statements)
5
103
0
Order By: Relevance
“…It has been observed that the severity of the injury determines the path by which cell death is realized, indicating a possible role for PRRs in guiding cell fate decisions by integrating signals from the microenvironment ( 21 ). Various currently recognized forms of PCD ( 18 , 22 ), including necroptosis, pyroptosis, ferroptosis, mitochondrial permeabilization transition (MPT)-mediated regulated necrosis, and parthanatos are initiated as a response to hypoxic injury, either directly or indirectly, and blocking their crucial pathways during the early phase of IRI generally leads to reduced necrotic (tubular) damage, reduced inflammation, preservation of renal function, and reduced mortality ( 15 ).…”
Section: Aki and Experimental Ischemia-reperfusion Injurymentioning
confidence: 99%
“…It has been observed that the severity of the injury determines the path by which cell death is realized, indicating a possible role for PRRs in guiding cell fate decisions by integrating signals from the microenvironment ( 21 ). Various currently recognized forms of PCD ( 18 , 22 ), including necroptosis, pyroptosis, ferroptosis, mitochondrial permeabilization transition (MPT)-mediated regulated necrosis, and parthanatos are initiated as a response to hypoxic injury, either directly or indirectly, and blocking their crucial pathways during the early phase of IRI generally leads to reduced necrotic (tubular) damage, reduced inflammation, preservation of renal function, and reduced mortality ( 15 ).…”
Section: Aki and Experimental Ischemia-reperfusion Injurymentioning
confidence: 99%
“…This Special Issue covers research articles that investigated the molecular mechanisms of inflammation [1][2][3] and injury [4,5] during different renal pathologies and renal regeneration [6], diagnostics using new biomarkers [7][8][9], and the effects of different stimuli like medication or bacterial components on isolated renal cells or in vivo models [10][11][12], all of which were summarized in a very simplified manner. Furthermore, this Special Issue contains important reviews that dealt with the current knowledge of cell death and regeneration [13,14], inflammation [15][16][17][18], and the molecular mechanisms of kidney diseases [19][20][21][22]. In addition, the potential of cell-based therapy approaches that use mesenchymal stromal/stem cells (MSCs) or their derivates is summarized [23][24][25].…”
mentioning
confidence: 99%
“…Priante and co-workers reviewed the different modalities of apoptosis, necrosis, and regulated necrosis in kidney injuries in order to find evidence for the role of cell death, which may pave the way for new therapeutic opportunities [14]. Others discussed the molecular basis of injury and repair in distinct cell types of the kidney during arterial hypertension [21].…”
mentioning
confidence: 99%
“…AKI refers to a rapid decline in renal function in a short period of time and leads to the accumulation of metabolic waste ( 148 ). AKI primarily affects renal tubules.…”
Section: Diseases and Protein Acetylation And Deacetylationmentioning
confidence: 99%